2019
DOI: 10.3389/fonc.2019.01014
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Ghrelin to Cancer; Attempts to Unravel an Apparent Controversy

Abstract: Ghrelin is an endogenous peptide hormone mainly produced in the stomach. It has been known to regulate energy homeostasis, stimulate secretion of growth hormone, and mediate many other physiologic effects. Various effects attributed to ghrelin contribute to many aspects of cancer development and progression. Accordingly, a large body of evidence has emerged about the association of ghrelin with several types of cancer in scales of cell-line, animal, and human studies. However, existing data are controversial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 142 publications
(293 reference statements)
0
31
0
Order By: Relevance
“…The data support that the studied radiometal Ghrelin inverse agonists could be used for the imaging of functional expression of Ghrelin receptors in vivo that these radiotracers have the potential to gain a deeper understanding on Ghrelin and its receptors in vivo in health and disease, in particular, in cancer [ 31 ]. The Ghrelin binding, constitutively active growth hormone secretagogue receptor type 1a (GHS-R1a) has been imaged and quantified by the developed novel compounds, structurally based on the potent inverse agonist KK-(D-1-Nal)-FwLL-NH 2 that were evaluated for receptor binding and efficacy in vitro .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The data support that the studied radiometal Ghrelin inverse agonists could be used for the imaging of functional expression of Ghrelin receptors in vivo that these radiotracers have the potential to gain a deeper understanding on Ghrelin and its receptors in vivo in health and disease, in particular, in cancer [ 31 ]. The Ghrelin binding, constitutively active growth hormone secretagogue receptor type 1a (GHS-R1a) has been imaged and quantified by the developed novel compounds, structurally based on the potent inverse agonist KK-(D-1-Nal)-FwLL-NH 2 that were evaluated for receptor binding and efficacy in vitro .…”
Section: Discussionmentioning
confidence: 61%
“…Although widely studied as a promising drug target, our knowledge about Ghrelin signaling, behavior, dynamic interactions with its receptor and functional receptor expression in vivo is still limited and basic bioscientific research is warranted to further evaluate the safety and benefits of Ghrelin drug treatment in patients with cancer [31][32][33]. In vivo imaging of the Ghrelin receptor should help to improve our understanding of its mode of action and might become a powerful tool for diagnosis and drug development [26,34].…”
Section: Research Papermentioning
confidence: 99%
“…Ghrelin is an endogenous peptide hormone mainly produced in the stomach. Previous research has shown that ghrelin can be a promising therapeutic option for cancer cachexia [ 49 ]. In addition, the KD genes were also enriched in functions related to cell growth, development and metabolism, such as “Biosynthetic process”, “Negative regulation of biological process” and “Cellular macromolecule metabolic process”.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, ghrelin has been shown to have a strong anti-inflammatory effect in many organs in both experimental and human models of diseases [66,67], which may help pancreatic beta cells to proliferate and be more functional. All of these factors, coupled with its ability to stimulate growth hormone [68], mean that it is therefore logical that ghrelin would be able to stimulate pancreatic beta cell proliferation. Studies have shown that ghrelin can stimulate GLP-1 [69], which in turn increases pancreatic beta cell mass via a large variety of mechanisms [47].…”
Section: Body Weight Gain Blood Glucose and Glucose Tolerancementioning
confidence: 99%